Getting to bail-in: Effects of creditor participation in European Bank restructuring - Alexander Schäfer; Isabel Schnabel; Beatrice Weder di Mauro (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2014)
[Introduction ...]This paper is structured as follows. The next chapter outlines the selected bail-in cases and formulates the hypotheses regarding expected market reactions. Chapter 3 covers the methodology. We introduce our identification procedure for the event selection, comment on the data sample and describe our empirical model. The fourth chapter contains the results for the bail-in events in chronological order, while chapter 5 provides a robustness analysis. Chapter 6 summarizes and concludes.
Additional information: Background Paper for the German Council of Economic Experts, October 31, 2014
Keywords: 330